Thermal excitation spectrum from entanglement in an expanding quantum string - Berges, Jürgen; Flörchinger, Stefan; Venugopalan, Raju (Arxiv, 2018)
A region of an expanding relativistic QCD string is entangled with the complement region of Minkowski space. We discuss how this leads locally to a reduced mixed state density matrix and quantify the amount of entanglement in terms of the entanglement entropy. For very early Bjorken time $τ$ we find that the entanglement entropy is extensive and scales with the rapidity. Remarkably, at these early times, the reduced density matrix is of thermal form with a temperature $T=\hbar/(2π τ)$, even in the absence of any scatterings.
Gesehen am 26.06.2018
V1: 17 Jul 2017, last revised 6 Feb 2018